Next Generation CAR T Cells for the Immunotherapy of High-Grade Glioma - Petersen, Christopher T.; Krenciute, Giedre (Frontiers in Oncology, 2019)
High grade gliomas (HGG) comprise a heterogeneous group of brain malignancies with dismal prognosis. Current standard-of-care includes radiation, chemotherapy, and surgical resection when possible. Despite advances in each of these treatment modalities, survival rates for pediatric and adult HGG patients has remained largely unchanged over the course of several years. This is in stark contrast to the significant survival increases seen recently for a variety of hematological and other solid malignancies. The introduction and widespread use of immunotherapies have contributed significantly to these survival increases, and as such these therapies have been explored for use in the treatment of HGG. In particular, chimeric antigen receptor (CAR) T cell therapy has shown promise in clinical trials in HGG patients. However, unlike the tremendous success CAR T cell therapy has seen in B cell leukemia and lymphoma treatment, the success in HGG patients has been modest at best. This is largely due to the unique tumor microenvironment in the central nervous system, difficulty in accessing the tumor site, and heterogeneity in target antigen expression. The results of these features are poor CAR T cell proliferation, poor persistence, suboptimal cytokine secretion, and the emergence of antigen-loss tumor variants. These issues have called for the development of “next generation” CAR T cells designed to circumvent the barriers that have limited the success of current CAR T cell technologies in HGG treatment. Rapid advancements in gene editing technologies have provided several avenues for CAR T cell modification to enhance their efficacy. Among these are cytokine overexpression, gene knock-out and knock-in, targeting of multiple antigens simultaneously, and precise control of CAR expression and signaling. These “next generation” CAR T cells have shown promising results in pre-clinical models and may be the key to harnessing the full potential of CAR T cells in the treatment of HGG.